Land and Survey Department, Miri / Nur Almas Ahmad Shamsudin - Ahmad Shamsudin, Nur Almas (2013)
Land and Survey Department Sarawak is an organization that handles and manage Sarawak land as a whole. Land and Survey Department Sarawak, whether formal or informal, comprises an extensive range ofsystems and processes to administer. The main processes of Land and Survey Department Sarawak include the transfer ofrights inland from one party to another through sale, lease, loan, gift and inheritance; the regulating of land and property development and the use and conservation ofthe land. Furthermore, this organization is gathering of revenues from the land through sales, leasing, and taxation; and the resolving of conflicts concerning the ownership and the use ofland. Basically, Land and Survey Department Sarawak functions may be divided into four components; juridical, regulatory, fiscal, and information management. These functions of land administration may be organized in terms of agencies responsible for surveying and mapping, land registration, and land valuation. Essentially, the functions of Land And Survey Department Sarawak is subject to the direction of the Yang Di-Pertua Negeri . Land in Sarawak is administered in accordance with the provisions of the mining ordinance and the subdivision of land is administered in accordance with the land (control of subdivision) ordinance, the public parks and greens ordinance, 1993 and the strata titles ordinance. On the other hand, under the terms ofthe inter-governmental committee report and the constitution of Malaysia, land and cadastral surveys are state subjects which come under the portfolio ofthe minister ofresource and planning management.